Serum level of nerve growth factor is a potential biomarker of conversion to bipolar disorder in women with major depressive disorder. Issue 9 (1st July 2019) - Pedrotti Moreira, Fernanda; Cardoso, Taiane C.; Mondin, Thaíse C.; Wiener, Carolina D.; de Mattos Souza, Luciano D.; Oses, Jean P.; Jansen, Karen; da Silva, Ricardo A.
Abstract : Aim: The aim of this study was to identify biomarkers associated with major depressive disorder (MDD) and conversion from MDD to bipolar disorder (BD) in an outpatient sample of women. Methods: This was a longitudinal study including women diagnosed with MDD and aged 18 to 60 years. The follow‐up was 3 years. The diagnosis was performed using the Mini International Neuropsychiatric Interview Plus. Blood collection was just performed in the first phase. Serum interleukin‐6, tumor necrosis factor‐α, brain‐derived neurotrophic factor, glial cell‐derived neurotrophic factor, and nerve growth factor (NGF) levels were measured using a commercial immunoassay kit. Results: We included 156 women. The conversion rate from MDD to BD was 15.4% ( n = 24). NGF serum levels were increased in patients who converted to BD compared to the remitted MDD group and current MDD group ( P = 0.013). The Bonferroni post‐hoc test for multiple comparisons revealed significant differences for higher NGF levels in patients who converted to BD compared to patients with current MDD ( P = 0.037). Interleukin‐6, tumor necrosis factor‐α, brain‐derived neurotrophic factor, and glial cell‐derived neurotrophic factor serum levels did not differ among the groups. Conclusion: Our results suggest that NGF might be a useful biomarker associated with early detection of conversion to BD, helping clinicians in the clinical diagnosis.